2000
DOI: 10.1103/physreve.61.1975
|View full text |Cite|
|
Sign up to set email alerts
|

Shock compression of condensed matter using intense beams of energetic heavy ions

Abstract: In this paper is presented, with the help of sophisticated two-dimensional hydrodynamic simulations, a suitable design with optimized parameters for a heavy-ion beam-matter interaction experiment that will be carried out at the Gesellschaft fur Schwerionenforschung (GSI) Darmstadt by the end of the year 2001 when the upgrade of the existing accelerator facility will be completed. Our simulations show that this upgraded heavy-ion beam is capable of generating strong shocks in solid targets that compress the tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 76 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…Currently the scientific community shows great interest in warm dense matter phenomena, which are studied with intense laser and particle beams. Most of this work does address basic physics issues of matter under extreme conditions Ni, et al, 2008;Piriz et al, 2002Piriz et al, , 2003aPiriz et al, , 2003bPiriz et al, , 2005Piriz et al, , 2006Piriz et al, , 2008Tahir et al, 1999Tahir et al, , 2000aTahir et al, , 2000bTahir et al, , 2001aTahir et al, , 2001bTahir et al, , 2003Tahir et al, , 2004Tahir et al, , 2005bTahir et al, , 2005cTahir et al, , 2006Tahir et al, , 2007aTahir et al, , 2007bTahir et al, , 2008bTahir et al, , 2009aTahir et al, , 2009bTemporal et al, 2003Temporal et al, , 2005 or is related to inertial fusion physics (Bangerter et al, 1982;Deutsch, 1986;Logan et al, 2008;Long & Tahir, 1982, 1986, 1987Piriz & Wouchuk, 1992;Tahir & Long, 1982, 1983, 1984. …”
Section: Hydrodynamic Simulation Resultsmentioning
confidence: 99%
“…Currently the scientific community shows great interest in warm dense matter phenomena, which are studied with intense laser and particle beams. Most of this work does address basic physics issues of matter under extreme conditions Ni, et al, 2008;Piriz et al, 2002Piriz et al, , 2003aPiriz et al, , 2003bPiriz et al, , 2005Piriz et al, , 2006Piriz et al, , 2008Tahir et al, 1999Tahir et al, , 2000aTahir et al, , 2000bTahir et al, , 2001aTahir et al, , 2001bTahir et al, , 2003Tahir et al, , 2004Tahir et al, , 2005bTahir et al, , 2005cTahir et al, , 2006Tahir et al, , 2007aTahir et al, , 2007bTahir et al, , 2008bTahir et al, , 2009aTahir et al, , 2009bTemporal et al, 2003Temporal et al, , 2005 or is related to inertial fusion physics (Bangerter et al, 1982;Deutsch, 1986;Logan et al, 2008;Long & Tahir, 1982, 1986, 1987Piriz & Wouchuk, 1992;Tahir & Long, 1982, 1983, 1984. …”
Section: Hydrodynamic Simulation Resultsmentioning
confidence: 99%
“…Theoretical work has shown that the SIS100 beam will deposit 150 kJ/g specific energy and 3 TW/g specific power in solid matter that will make it possible to access the unexplored regions of the phase diagram (Tahir et al 1998(Tahir et al , 1999(Tahir et al , 2000a(Tahir et al , 2000b(Tahir et al , 2000c(Tahir et al , 2001a. Four different types of experiments have been designed to study different interesting problems in the area of HED Physics.…”
Section: The Hedgehob Scientific Proposalmentioning
confidence: 99%
“…Over the past decade, extensive theoretical work that included two-and three-dimensional numerical simulations as well as analytic models, has been carried out to investigate the phenomena of beam-target heating (Tahir et al 1998(Tahir et al , 1999(Tahir et al , 2000a(Tahir et al , 2000b(Tahir et al , 2000c(Tahir et al , 2001a(Tahir et al , 2001b(Tahir et al , 2003a(Tahir et al , 2003b(Tahir et al , 2005a(Tahir et al , 2005b(Tahir et al , 2005cPiriz et al 2002Piriz et al , 2003aPiriz et al , 2003bPiriz et al , 2005Piriz et al , 2006aPiriz et al , 2006bPiriz et al , 2008Piriz et al , 2009Temporal et al 2005;Lopez Cela et al 2006) in order to design novel experiments to study High Energy Density (HED) Physics using the SIS100 uranium beam. These studies have shown that particle beams have a number of advantages over other drivers.…”
Section: Introductionmentioning
confidence: 99%
“…Thus it is obvious, that high energy density induced by heavy ion beams requires an intense bunch of short time duration (τ B ) which is focused into a sample with a small focal spot size (Tahir et al 2001b). However, during the time the beam heats the sample, hydrodynamic response resulting in an expansion of the target material sets in.…”
Section: High Energy Density Physicsmentioning
confidence: 99%